Pengaruh Konsentrasi Tepung Wortel (Daucus carota L.) Pada Pakan Terhadap Peningkatan Warna Ikan Koi (Cyprinus carpio) - Arnol Hasudungan Pardosi; Syammaun Usman; Indra Lesmana (AQUACOASTMARINE, 2016)
Koi (Cyprinus carpio) is a type of fish that can be cultivated to serve asornamental fish. As ornamental fish, koi fish that have beautiful and bright colors canbe high value. Color is one of the reasons ornamental fish demand by the public, sofarmers need to retain the color of ornamental fish that is by giving feed containingpigments. The work done to obtain a uniform bright colors in fish is added to thepigment in the feed source. Source of natural pigments can be obtained from flour carrot(Daucus carota L.). The purpose of this study was to determine the dose of carrot flourthat can enhance the color of koi fish. This study used a completely randomized design(CRD) with three replications, with doses of 0%, 1%, 3%, and 5% for 30 days. Theaddition of carrot powder through the feed can improve the color of koi fish. Givingcarrot flour with a dose of 5% produces a brighter color than the other doses. CarrotsFlour Addition on the feed had no effect on the weight and length growth koi fish.Keywords: Fish Koi, Cyprinus carpio, Color Enhancement, Daucus carota L.